Pembuatan Video Edukasi Bijak Bermedia Sosial Bagi Masyarakat Desa Jagasatru Kabupaten Cirebon - Imam Lewi Silalahi; Desto Samro Johannes Sinaga; Albertus Yan Rayen Mulyadi Putra; Marselinus Firstio Ivan Xaveri; Sukma Iva Frederick (Publikasi Indonesia, 2022)
We do this community service activity to provide education about social media wisdom to the people of Jagasatru Village, Pekalipan District, Cirebon Regency. This service needs to be done because the people of Jagasatru Village often experience anxiety due to the spread of hoax information and other social media problems such as provocation actions. Based on the observations made, the people of Jagasatru Village, Pekalipan District, began to actively use social media in their daily lives. Starting from children to the elderly, It is undeniable that this pandemic has resulted in a significant increase in the use of social media. For this reason, education is needed to help the people of Jagasatru Village by making educational videos about using social media wisely. The methods used in this service include socialization with counseling techniques by providing material in the form of educational videos and power points about social media wisdom given to the people of Jagasatru Village by as many as 30 people. In addition, the data collection technique used is quantitative by conducting interviews to obtain information, then giving a post test, and then it will be analyzed descriptively and displayed in the form of a diagram. This dedication has resulted in an increase in public understanding of using social media wisely in everyday life. Besides that, the use of social media can provide good benefits.